Independent, corroborating evidence continues to accumulate that post-exercise cooling diminishes muscle adaptations to strength training - Peake, J. M. (The Journal of Physiology, 2019)
Recovery after exercise is a fundamental principle of exercise training. Whether it is between training sessions or competitive events (that may be separated by several hours, or alternatively, several days), the overarching goal of recovery is to restore homeostasis. A key assumption underpinning the benefits of regular post-exercise recovery is that it will assist athletes to train more effectively, or compete at higher levels. Cold water immersion (CWI) is a popular strategy to recover from intense exercise, based on several proposed mechanisms: cutaneous vasoconstriction, increased central blood volume, lower cardiovascular strain, greater efflux of metabolites from muscle, reduced muscle temperature, soreness and swelling. An important issue that has emerged over the last decade or so is whether these physiological effects of CWI promote - or hinder - long-term adaptation to exercise training.